2007
DOI: 10.1590/s1516-35982007000400019
|View full text |Cite
|
Sign up to set email alerts
|

Suplementação de lipídeos de diferentes fontes em dietas para vacas Jersey na fase inicial de lactação

Abstract: RESUMO -Objetivou-se avaliar os efeitos da suplementação de lipídeos como sais de cálcio de óleo de palma (GP), farelo de arroz integral + óleo de arroz (FAIO) ou farelo de arroz integral + sebo bovino (FAIS) sobre o consumo de MS, a eficiência produtiva e o balanço energético de vacas leiteiras no terço inicial da lactação. A dieta controle continha 2,9% EE, enquanto as dietas GP, FAIO e FAIS continham, respectivamente, 5,13; 5,29 e 5,16% EE. Foram utilizadas oito vacas Jersey, puras de origem, de 2 a e 3 a o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…Duarte et al (2005) did not find any effects of the supplementation or the source of fat used on DMI in dairy cows. The mean DMI (15.7 kg/day) observed in this work was similar to the 15.9 and 16.1 kg/day found by Borba et al (2006) and Costa et al (2007), respectively. These authors also worked with sources of lipids for lactating cows.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Duarte et al (2005) did not find any effects of the supplementation or the source of fat used on DMI in dairy cows. The mean DMI (15.7 kg/day) observed in this work was similar to the 15.9 and 16.1 kg/day found by Borba et al (2006) and Costa et al (2007), respectively. These authors also worked with sources of lipids for lactating cows.…”
Section: Discussionsupporting
confidence: 92%
“…According to the results of Borba et al (2006), Freitas Júnior et al (2010, and the present work, levels of up to 80 g/kg of EE in the diet do not interfere with the production, and the producer may opt for the diet that is most economic. Costa et al (2007) reported increased corrected milk production when using diets with 50.0 g/kg of EE containing protected oil, whole rice meal plus rice oil, and whole rice meal plus bovine tallow as sources of lipids. This increase in production when using lipids in the diet is related to the increased ingestion of energy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this aspect, positive results for milk yield with fat-supplemented diets were obtained by Costa et al (2007) and absence of responses by Eifert et al (2006), Huang et al (2008), and Ganjkhanlou et al (2009).…”
Section: Discussionmentioning
confidence: 96%